Functional genomics of tomato for the study of plant immunity - Rosli, Hernan Guillermo (2015)
Tomato (Solanum lycopersicum), along with many other economically valuable species, belongs to the Solanaceae family. Understanding how plants in this family defend themselves against pathogens offers the opportunity of improving yield and quality of their edible products. The use of functional genomics has contributed to this purpose through both trad- itional and recently developed techniques that allow determination of changes in transcript abundance during pathogen attack. Such changes can implicate the affected gene as participating in plant defense. Testing the involvement of these candidate genes in defense has relied largely on posttranscriptional gene silencing, particularly virus-induced gene silenc- ing. We discuss how functional genomics has played a key role in our current understanding of the defense response in tomato and related species and what are the challenges and opportunities for the future.